ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETERNAK RAKYAT SAPI POTONG DI KECAMATAN LAMPASIO KABUPATEN TOLITOLI PROVINSI SULAWESI TENGAH - Ibrahim Ibrahim; Supamri Supamri; Zainal Zainal (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2020)
This research aims to determine the factors affected the income of farmer in business of beef cattle in Lampasio district, Tolitoli regency. This research applied purposive sampling technique in choosing sample. There were 36 selected sampless as respondents of three districts: Sibea, Lampasio, and Tinading. The observed variables were the characteristics of respondents’ income such as breeders’ age. Level of education, number of family, and farming experinence. The multiple regression was employed to find out the significant effect of the farmer income. The result showed that farmer age is old with low education level, with more than 7 years experience. The coefficient value of R by 0,131which means that observed variables was 13,1% whereas the value of unobserved variables in this research was 86,9%. Eventhough there is no significant variable effect to farmer income, the education effects positvively to farmer income. Keywords: income, beef cattle, multiple regression